Epidemio-therapeutic Survey on Malnourished Children Aged 0-5 Years Old in the Gbado-Lite Health Zone (Nord Ubangi Province, Democratic Republic of the Congo) - Koto-te-Nyiwa Ngbolua; Guy Kumbali Ngambika; Blaise Mbembo-wa-Mbembo; Ruphin Djolu DJoza; Gédéon Ngiala Bongo; Falanga Mawi Clarisse; Benjamin Gbolo Zoawe; Masengo Ashande Colette; Libwa Momi Tabonge Bertin (Britain International of Exact Sciences (BIoEx) Journal, 2019)
Child malnutrition is one cause of death worldwide, but the greatest burden is borne by African countries, particularly in Sub-Saharan Africa. The Democratic Republic of Congo, despite its wealth of biodiversity, is confronted with this phenomenon which seriously hinders its development. A cross-sectional descriptive study was conducted in The Nord Ubangi Province from 01 to 31 December 2016 on a population of 133 malnourished children aged 0 to 5. The results show that the 2 to 3 year old age group (25-36 months) was the most affected by malnutrition. The most affected children were male, at 52.63%. Most of these children, 24.8%, resided in rural areas around Gbadolite. The majority of their parents, 61.6%, was farmers or only engaged in housework. 78.9% of respondents had edema in their bodies, and 91.7% did not meet the appetite test. These children were subjected to antibacterial treatment outside of ready-to-use therapeutic foods (ATPE). After this treatment, the cure rate was satisfactory at 73.6%.